Homogenization of variational inequalities of Signorini type for the p-Laplacian in perforated domains when p ∈ (1, 2) - Díaz, JI; Gómez-Castro, D; Podolskiy, AV; Shaposhnikova, TA (Springer, 2017)
The asymptotic behavior, as ε → 0, of the solution uε to a variational inequality with nonlinear constraints for the p-Laplacian in an ε-periodically perforated domain when p ∈ (1, 2) is studied.